TANTANGAN AKAD KAFALAH SEBAGAI INSTRUMEN PENJAMINAN KREDIT SYARIAH - Reza Mutawakkil Alalloh; Imron Mustofa (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2024)
This research aims to analyze the effectiveness of the kaf?lah contract as a credit guarantee instrument in sharia financial institutions in Indonesia, as well as identifying the challenges faced in its implementation. The method used is a qualitative approach with library research techniques, where researchers collect and analyze various relevant literature sources, including books, journal articles and related legal documents. The research results show that the kaf?lah contract functions as a solution for customers who do not have conventional collateral, by emphasizing the principles of mutual assistance and collective responsibility in accordance with sharia values. Other than that, this agreement could improve financial inclusion, particularly for MSMEs, which frequently face barriers to loan availability. Implementing the kaf?lah contract is still hampered by issues like the general public's poor comprehension of it and the requirement for stricter and more precise laws. In order for kaf?lah contracts to assist sharia economic growth in Indonesia, comprehensive research and efforts are required to improve knowledge and preparedness of sharia financial institutions. It is intended that this study would further the theory and application of credit guarantees in Islamic financial institutions and offer suggestions for further advancements.